FACTORS INFLUENCING DOCTORS’ COMPLIANCE IN COMPLETING ELECTRONIC MEDICAL RECORDS AT OUTPATIENT POLYCLINICS - Ndoen, Nelci; Adu, Apris A.; Berek, Noorce Ch.; Roga, Anderias Umbu; Nayoan, Christina R. (HEARTY, 2026)
Digital transformation in healthcare through the implementation of Electronic Medical Records (EMR) aims to improve service quality, documentation efficiency, and patient safety. However, physician compliance in completing EMRs at the Outpatient Clinic of Prof. Dr. W. Z. Johannes Kupang Hospital remains low, with only 28.9% categorized as compliant. This study aimed to analyze factors influencing physician compliance in EMR completion based on the Theory of Planned Behavior (TPB), including attitude, subjective norms, perceived behavioral control, and intention. A cross-sectional design was employed with a total sample of 38 attending physicians using validated and reliable questionnaires and observation checklists. Data were analyzed using Chi-square tests and logistic regression. The findings showed that attitude (p=0.015; PR=0.049) and intention (p=0.022; PR=0.052) significantly affected physician compliance. Physicians with negative attitudes and weak intentions had a higher risk of non-compliance. Meanwhile, subjective norms (p=0.836; PR=1.333) and perceived behavioral control (significant only in bivariate analysis) did not influence compliance. Technical barriers such as inadequate facilities, limited system integration, and administrative workload also contributed to low compliance levels. This study concludes that internal factors particularly attitude and intention play a more dominant role in determining physician compliance than external pressures or organizational support. Strengthening perceived benefits, improving system usability, and providing adequate training are essential to enhance physician compliance in EMR completion.